The Impact of Job Satisfaction on Turnover Intention: A Study of Generation Z Employees (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This research investigates the relationship between job satisfaction and turnover intention among Generation Z employees working in an edutainment company. Recognized for their digital expertise, high expectations, and generally low organizational loyalty, Generation Z employees are often associated with elevated turnover rates. To examine this phenomenon, the study adopts a quantitative method using a census sampling technique, gathering responses from 56 Gen Z employees through a structured questionnaire. Job satisfaction was assessed through five dimensions: salary, promotion opportunities, coworker relationships, the nature of the work, and supervisory support. Meanwhile, turnover intention was evaluated using three indicators: the frequency of thoughts about leaving, the desire to seek alternative employment, and the actual intention to resign. The collected data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach. The analysis revealed a strong and statistically significant negative relationship between job satisfaction and turnover intention (β = –0.858, p < 0.001), indicating that higher job satisfaction substantially reduces the likelihood of employees wanting to leave. Additionally, the model demonstrated a high explanatory power with an R² value of 0.736, suggesting that job satisfaction accounts for a considerable portion of the variance in turnover intention. Among the five job satisfaction dimensions, supervision emerged as the most influential factor in retaining Generation Z employees. These findings provide valuable insights into the work attitudes of Generation Z, emphasizing the importance of effective managerial support in fostering employee satisfaction and reducing turnover. The study offers practical implications for edutainment companies and similar industries, highlighting the need to develop targeted strategies that enhance job satisfaction, particularly in terms of leadership and workplace culture, in order to retain young talent in a competitive labor market.